Ethics and the Accounting Publishing Process: Author, Reviewer, and Editor Issues - Borkowski, Susan C. (Journal of business ethics, 1998)
Are codes of ethics needed to guide author, reviewer and editor publishing practices in accounting journals? What practices are considered unethical, and to what extend do they occur? A survey of ninety-five journal editors who publish accounting articles rated author, reviewer and editor practices as ethical or unethical, and estimated the frequency with which these practices occur. Respondents also commented on current publishing practices regarding the double-blind review process, payments for reviews, confirmatory bias, and whether codes of ethics are needed for the publication process. More than half the editors supported the status quo, and felt that that codes were not necessary for editors and reviewers. They were evenly split on the question of an author code of ethics.